2002
DOI: 10.1002/ajh.10192
|View full text |Cite
|
Sign up to set email alerts
|

PAI‐1 gene 4G/5G genotype: A risk factor for thrombosis in vessels of internal organs

Abstract: Although the common 4G/5G polymorphism in the promoter of the PAI-1 gene was suggested to be a risk factor for some of the thrombotic disorders, its significance in the development of thrombosis is still controversial. This study presents the data on a total of 357 patients with different types of thrombosis and 281 unrelated healthy controls. It was found that the 4G/4G genotype is associated with a higher risk of thrombosis (OR, 1.7; 95% CI, 1.1-2.5). Patients were divided into five distinct groups according… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
48
1
14

Year Published

2004
2004
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(68 citation statements)
references
References 17 publications
5
48
1
14
Order By: Relevance
“…Hypofibrinolysis because of increased plasminogen activator inhibitor-1 (PAI-1) plasma concentrations has been identified as a risk factor [1][2][3]. Yet only very limited and at least partly conflicting data on the role of gene polymorphism known to affect PAI-1 plasma levels are available [2][3][4]. Recently, Gori et al [2] investigating 112 patients with RVO suggested both homozygosity for the angiotensin converting enzyme insertion/deletion (ACE I/D) polymorphism and the combined presence of the PAI-1 4G/4G and ACE DD genotypes as novel risk factors.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Hypofibrinolysis because of increased plasminogen activator inhibitor-1 (PAI-1) plasma concentrations has been identified as a risk factor [1][2][3]. Yet only very limited and at least partly conflicting data on the role of gene polymorphism known to affect PAI-1 plasma levels are available [2][3][4]. Recently, Gori et al [2] investigating 112 patients with RVO suggested both homozygosity for the angiotensin converting enzyme insertion/deletion (ACE I/D) polymorphism and the combined presence of the PAI-1 4G/4G and ACE DD genotypes as novel risk factors.…”
mentioning
confidence: 99%
“…Recent research indicates that PZ deficiency may predispose to adverse pregnancy outcome. Gris et al [4] have demonstrated that women with PZ deficiency have a 6.7-fold increased risk of fetal loss between gestational weeks 10 and 15. Further work has also linked anti-PZ antibodies to both fetal loss and severe pre- …”
mentioning
confidence: 99%
“…9 PAI-1 4G-4G has come out as the leader factor in the SVT group, and in the various subgroups, confirming its important role in pathogenesis of SVT, as Balta et al 10 have found, and confirming itself as a thrombotic risk factor in different target organs, as showed by Tsantes et al 11 MTHFR 677TT genotype was strongly associated with portal thrombosis in our cirrhotic patients as reported previously by Amitrano et al 12 Hardy-Weinberg equilibrium for PAI-1 and MTHFR 677 was deviated from that expected from a population (PAI-1 x 2 41.96, P < 0.0001; MTHFR 677 x 2 15.00, P 0.0001). We think that PAI-1 4G-4G and MTHFR 677TT can increase the inflammation response, participating to the activation of perisinusoidal hepatic stellate cells, causing hepatic fibrosis and augmented intrahepatic vascular resistance typical of the LC, as suggested by Fernandez.…”
Section: Discussionmentioning
confidence: 64%
“…Выявленный у больной аллельный вариант гена PAI-1 -675 4G повышает уровень продукции PAI-1 в крови, что приводит к подавлению фибринолитиче-ской активности крови и способствует формированию внутрисосудистых тромбов. Величина относительного риска тромбозов при наличии только этого полиморфиз-ма достигает 1,7 [18].…”
Section: Discussionunclassified